Vampirovibrio chlorellavorus draft genome sequence, annotation, and preliminary characterization of pathogenicity determinants. Issue 1 (17th July 2019) - Hovde, Blake T.; Steichen, Seth A.; Starkenburg, Shawn R.; Brown, Judith K.
SUMMARY: Vampirovibrio chlorellavorus is recognized as a pathogen of commercially‐relevant Chlorella species. Algal infection and total loss of productivity (biomass) often occurs when susceptible algal hosts are cultivated in outdoor open pond systems. The pathogenic life cycle of this bacterium has been inferred from laboratory and field observations, and corroborated in part by the genomic analyses for two Arizona isolates recovered from an open algal reactor. V. chlorellavorus predation has been reported to occur in geographically‐ and environmentally‐diverse conditions. Genomic analyses of these and additional field isolates is expected to reveal new information about the extent of ecological diversity and genes involved in host‐pathogen interactions. The draft genome sequences for two isolates of the predatory V. chlorellavorus ( Cyanobacteria ; Ca. Melainabacteria ) from an outdoor cultivation system located in the Arizona Sonoran Desert were assembled and annotated. The genomes were sequenced and analyzed to identify genes (proteins) with predicted involvement in predation, infection, and cell death of Chlorella host species prioritized for biofuel production at sites identified as highly suitable for algal production in the southwestern USA. Genomic analyses identified several predicted genes encoding secreted proteins that are potentially involved in pathogenicity, and at least three apparently complete sets of virulence (Vir) genes, characteristic of the VirB‐VirD type system encoding the canonical VirB1‐11 and VirD4 proteins, respectively. Additional protein functions were predicted suggesting their involvement in quorum sensing and motility. The genomes of two previously uncharacterized V. chlorellavorus isolates reveal nucleotide and protein level divergence between each other, and a previously sequenced V. chlorellavorus genome. This new knowledge will enhance the fundamental understanding of trans ‐kingdom interactions between a unique cosmopolitan cyanobacterial pathogen and its green microalgal host, of broad interest as a source of harvestable biomass for biofuels or bioproducts.